2007
DOI: 10.2466/pr0.101.2.565-573
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acculturation, Sex, and Heavy Alcohol use in Latino College Students

Abstract: 24% of 917 students at California State University Long Beach who completed an alcohol use survey in 2002 (73% response) identified themselves as Latino. Because measures of acculturation reported in most adult studies positively correlated with alcohol use and sex, it was hypothesized that these associations might also apply to Latino college students. With increasing levels of acculturation, women but not men in this Latino college sample reported significantly greater occurrence of heavy drinking, positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In line with this assertion, when examining gender as a moderator, we found that gender moderated the association between acculturation and the amount of alcohol consumed while pregaming such that lower U.S. acculturation was associated with increased alcohol consumption while pregaming for Latino men whereas a different pattern was observed for Latinas. This pattern of associations is consistent with previous research linking higher levels of acculturation with increased alcohol consumption levels among Latino/a men and women (e.g., Raffaelli et al, 2007; Safer & Piane, 2007; Zamboanga et al, 2006). As illustrated in the figure, the relations between U.S. acculturation and pregaming quantity among women was weak, however, particularly when compared to the strong, inverse relations between the same two variables for men.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with this assertion, when examining gender as a moderator, we found that gender moderated the association between acculturation and the amount of alcohol consumed while pregaming such that lower U.S. acculturation was associated with increased alcohol consumption while pregaming for Latino men whereas a different pattern was observed for Latinas. This pattern of associations is consistent with previous research linking higher levels of acculturation with increased alcohol consumption levels among Latino/a men and women (e.g., Raffaelli et al, 2007; Safer & Piane, 2007; Zamboanga et al, 2006). As illustrated in the figure, the relations between U.S. acculturation and pregaming quantity among women was weak, however, particularly when compared to the strong, inverse relations between the same two variables for men.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this suggestion, Raffaelli and colleagues (2007) found that orienting toward the U.S. culture was positively associated with frequency of alcohol use for women whereas the opposite was found for men. Another study showed similar associations for Latina women with respect to the occurrence of heavy drinking being related to U.S. practices, but not for Latino men (Safer & Piane, 2007). Using a bidimensional approach to acculturation, Ceballos, Czyzewska, and Croyle (2012) found that higher levels of U.S. acculturation and lower levels of enculturation were associated with more frequent alcohol use among women; however, no such relations were found among men.…”
Section: Acculturation and Drinking Behaviorsmentioning
confidence: 84%
See 2 more Smart Citations
“…National data indicate Latina/os engage in heavier drinking than individuals from other ethnic minority groups (e.g., among adults, Cook & Caetano, 2014; among adolescents, Johnston, O’Malley, Miech, Bachman, & Schulenberg, 2017), and most studies on college students suggest similar trends (e.g., Glassman, Dodd, Sheu, Rienzo, & Wagenaar, 2010; Safer & Piane, 2007). Furthermore, Latina/os endorse more severe alcohol problems than non-Latina/o whites (e.g., Mulia, Ye, Greenfield, & Zemore, 2009), rendering examinations of mechanisms underlying drinking behavior in this group highly important.…”
mentioning
confidence: 99%